2022
DOI: 10.3389/fmed.2022.945011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Gender and 1-Year Mortality in ANCA-Associated Vasculitis Patients: A Single-Center Retrospective Analysis and Meta-Analysis

Abstract: ObjectiveThe relationship between gender and short-term prognosis of patients with anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV) is unclear, hence single-center retrospective analysis and meta-analysis were conducted to determine the relationship.MethodsInitially treated patients with AAV were retrospectively enrolled. Data of clinical manifestation, laboratory indicators, Birmingham vasculitis activity score (BVAS), therapeutic treatments, and the patients' situations within 1 year w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The scores were not influenced by AAV phenotype or disease duration. These results are comparable to those found by Robson et al [ 6 ], thus supporting the validity of a sex-based approach in AAV research [ 9 ]. Considering that disease activity was similar in our cohort [BVASv3: 0 (IQR 0–3)], the differences observed between sexes might have a clinically meaningful impact.…”
Section: Discussionsupporting
confidence: 90%
“…The scores were not influenced by AAV phenotype or disease duration. These results are comparable to those found by Robson et al [ 6 ], thus supporting the validity of a sex-based approach in AAV research [ 9 ]. Considering that disease activity was similar in our cohort [BVASv3: 0 (IQR 0–3)], the differences observed between sexes might have a clinically meaningful impact.…”
Section: Discussionsupporting
confidence: 90%
“…However, in terms of ALD, no research on their relationships has been reported yet. Although, among the parameters of ANI, the contribution of AST and male sex at diagnosis to the estimation of all-cause mortality was demonstrated in patients with systemic vasculitis to date [ 17 , 18 ]. Therefore, although ANI was developed as an index for distinguishing ALD from NAFLD, it could be reasonably speculated that ANI could be used to estimate poor outcomes during follow-up in patients with AAV.…”
Section: Introductionmentioning
confidence: 99%